Making internship policy a must [Sierra Leone] - Bassie, Ann-Marie; Palmer, Samuel; Nelson, Mary (Technical Centre for Agricultural and Rural Cooperation, 2018)
With high rates of unemployment, and a sharp decline in GDP in recent years, economic prospects for young people are limited. To address these challenges, the National Youth Commission (NAYCOM), the Ministry of Youth Affairs (MoYA), and the United Nations Development Programme (UNDP) established a Graduate Internship Programme (GIP) to boost the employability of graduates by increasing the number and quality of internships. So far, 70% of the 791 interns placed have acquired permanent jobs.